Remarks on Receiving the John W. Knutson Distinguished Service Award - Stephen Colchamiro, DMD, on behalf of Esther Colchamiro, DMD, MPH (Blackwell Synergy, 2003)
am truly honored to be accepting this award for Esther; but to be honest, I would prefer not to be here. I would much prefer to be sitting where you are-sitting, watching my aunt receive this wonderful prestigious award. I will be very brief, but Esther would have been even briefer. She would have modestly come up here, said thank you, and then given out her home-baked cookies to everyone. As David so beautifully described, that is her way of doing h g s ... quietly, efficiently, and with enormous results